Mississippian beginnings - Wilson, Gregory D. (Florida Museum of Natural History. Ripley P. Bullen series, 2018)
Using fresh evidence and non-traditional ideas, the contributing authors to 'Mississippian Beginnings' reconsider the origins of the Mississippian culture of the North American Midwest and Southeast (AD 1000-1600). They discuss signs of migrations, pilgrimages, violent conflicts, and other far-flung entanglements that now appear to have shaped the early Mississippian past.